Editorial to the Special Issue - Stefan Ederer; Eckhard Hein; Torsten Niechoj (Intervention. European Journal of Economics and Economic Policies, 2012)
First paragraph: The financial and economic crises which started in 2007 have triggered and motivated increasing research on finance and the instability of the financial system but also on the relationship between finance, distribution and growth. This special issue discusses various, but related theoretical and empirical aspects of finance, instability, distribution and investment.
Keywords: E02; 330